Assessment of pozzolanic activity of palm oil clinker powder. (30th November 2016) - Karim, Mohammad Razaul; Hashim, Huzaifa; Abdul Razak, Hashim
Highlights: A significant hump was observed in the angular 2θ range from 10° to 35°, representing an amorphous phase. Palm oil clinker is a pozzolanic material. Pozzolanic activity of palm oil clinker is higher than ground palm oil fuel ash. Abstract: Palm oil clinker (POC) is a waste material produced as result of using palm oil shell and mesocarp fibres as fuel to run stream turbines in palm oil mills. The current practice is to dump the waste in open land or landfill sites, which leads to environmental problems. The suitability of using the palm oil clinker powder (POCP) in concrete as well as blended cement largely depends on its pozzolanic activity. In the present study, the pozzolanic activity of POCP has been investigated using X-ray diffraction (XRD), thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR) techniques, and compressive strength activity index measurement. The microstructure of the hydrated cement paste was observed using field emission scanning electron microscopy (FESEM). In order to evaluate the pozzolanic activity of the POCP, the pastes were prepared with ordinary Portland cement (OPC) at the level of substitution of 30%. The fluidity of the paste was maintained at 110 ± 5 mm. The strength activity index was evaluated according to ASTM standard. The microstructure properties investigation found that the portlandite (Ca(OH)2 ) react with SiO2 of POCP and formed C-S-H gel for strength development. This observation and strength activity index result confirmed that POCP is a pozzolanic material.